Digital Health Literacy and Physical Activity Programme for Improvement of Quality of Life in Caregivers of People with Dementia (CAREFIT): Study Protocol - Ferrero-Sereno, Patricia; Palomo-López, Patricia; Mendoza-Muñoz, María; Luna-Castaño, Patricia; Caballero-De la Calle, Raquel; Muñoz-Bermejo, Laura (MDPI, 2025)
Abstract: Background/Objectives: Dementia involves progressive cognitive and functional deterioration that leads to dependence and overload on family caregivers. This overload has a negative impact on the physical, mental, emotional, and occupational health of caregivers, leading to occupational imbalance and problems arising from an inadequate distribution of time devoted to caregiving. This project aims to evaluate the effects of the technology-based CAREFIT programme, structured around physical activity interventions, education, and psychoemotional and social support, on the health-related quality of life and emotional well-being of informal caregivers. Methods: The experimental group will develop the intervention programme, which will last 8 weeks and combine educational activities, physical activities, and psychoemotional and social support. Before beginning the intervention, the entire experimental group will receive a training session and edu- cational materials on how to access and use the platform. The CAREFIT platform will consist of two educational sessions and two weekly physical sessions, combined with psychoemotional and social support activities that participants must complete. Initial, final, and follow-up evaluations will be conducted. The HRQoL and psychoemotional health (stress, anxiety, depression, and perceived social support and burden) of caregivers of people with dementia will be the main outcome measures. The effects of the intervention on the study variables will be assessed using a repeated-measures analysis of variance (ANOVA). Conclusions: The proposed protocol for the CAREFIT programme represents an innovative and multidisciplinary initiative that leverages a digital platform to promote the well-being of informal caregivers of people with dementia. This approach combines health literacy and strengthened psychoemotional and social support. Through this integration, the goal is to reduce the levels of burden, stress, anxiety, and depression among primary caregivers, while strengthening their self-care capabilities and social support networks.